The Analysis of Hydrophobic Interaction on Aspergillus Niger Xylanase Enzyme Thermal Stability - Malau, Nia Daniaty (Journal of Technomaterial Physics, 2019)
Xylanase is a type of enzyme that has an important role in the industrial field. One measure that can be done to improve the thermostability of an enzyme is by protein engineering. The mutation of the protein can be done by studying protein structures through molecular dynamics simulation approach. In this research, thermal stability analysis on Aspergilus niger Wild Type Xylase (AnX) was performed which aims to study the thermal stability characteristics of xynalase enzyme from Aspergillus niger through molecular dynamics simulation approach. AnX molecular dynamics simulation was performed by NAMD (Not Just Another Molecular Dynamic) software at 300 – 500 K. The research was focused on the study of enzyme thermal stability characteristics in order to get the information of residues accountable for such characteristics. The selection of residues to be mutated was based on hydrophocic interaction analysis. Then from that, the design of xylanase enzyme mutant with better thermostability than wild type xynalase enzyme was made in order to provide design reference for more stable xylanase mutation design which can be implemented in wet experiments for of Aspergillus niger Xylanase enzyme genetic engineering. The enzyme was unfolded at 500 K at 9.5 ns. The residues responsible of the thermal stability were based on hydrophobic interaction analysis in Alanin at residue 60. This residue is located in segmen/chain 3. The best mutant is Alanin 60 residue mutant which is replaced by Methionin and ∆∆Gsolv of -21.10345 was obtained. Thus, Ala60Met is the most stable mutant which might increase the thermal stability of Aspergillus niger Xylanase Enzyme.